Hubungan Mitos Pencegahan Infeksi Menular Seksual dengan Suspect Infeksi Menular Seksual pada Wanita Pekerja di Panti Pijat Kota Dumai - Hastuti Marlina (STIKes Hang Tuah Pekanbaru, 2014)
Sexually transmitted infection ( STI ) is an infection spread by sexual contact and non sexual caused variety of bacteria, virus parasait, fungi and ticks. According to the World Health Organitation (WHO) each year there are approximately 350 million new STI sufferer in a country grown including Indonesia where 15.4% occur in women sex workers. The purpose of this research was to find out how the behavior of the myth of the prevention of STI incidence in women workers at a massage parlor Dumai city. This type of research quantitative analytic with cross sectional design research. Sampling using total sampling by the number of respondents 40 people. Data collection using the questionnaire. Analysis of data by test chi square. The results showed 67.5% of respondents suspect infected with STI. Statistical tests are obtained results there were relationship behavior myths with STI prevention in women workers in a massage parlor. Myth of the variable washing genitals with SOAP, alcohol, soda water, water decoction of betel leaf, ginger juice before or after having sex with the suspect sexually transmitted Infection in women Working in a massage parlor has a value of POR (95% CI) of the 6.08 (1,540 - 23,992) sexually transmitted in women workers at a massage parlor Dumai. Expected health workers and NGOs particularly Dumai further enhance cooperation in enhancing women's knowledge workers in a massage parlor in order not to wrong perceptions about the myth of the prevention of STI